Metode Waste Assessment Model untuk Menetapkan Prioritas Perbaikan Sistem Persediaan Obat - Misra Hartati; Wahid Badru Zaman (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
There were seven waste of inventory system in district general hospital Arifin Achmad Riau Province i.e over volume drug procurement, over logistik inventory, drugs out of spesification, unnecessary motion, drugs transportation, innapropriate operation (long administration) and waiting order. Thats waste known as main cause drugs inventory sytem positive contribution not leave for patient service and hospital income. The problems related to seven waste are priority decision improvement for the right target and cost-effective. Priority decision would be solve use waste assessment model that separate into two main measure. The results showd first rank of waste evaluation soon were procurement inventory system in large quantities.Keywords: drugs, inventory system, waste assessment model